Peak-performance living - Robertson, Joel C., 1952- (HarperSanFrancisco, 1996)
For businesspeople, athletes, and anyone who wants to boost performance, lecturer, pharmacologist, and consultant to Fortune 100 corporations and professional sports teams Dr. Joel Robertson shares his proven secrets to help anyone feel supercharged - naturally and without drugs like Prozac. Clearly explaining the brain's chemistry and the stimuli that influence it, Robertson leads you through a series of questions designed to help you determine your neurochemistry and choose foods, behaviors, and exercises that can quickly and permanently enhance the way you feel.